ANALISIS SISTEM INFORMASI E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE DI BATAM - Situmorang, Robert (Jurnal PROFITA : Akuntansi dan Manajemen, 2025)
The development of information technology has brought major changes to the trade industry, including e-commerce. Shopee as one of the largest e-commerce platforms in Southeast Asia offers various information system features to improve user experience and influence their purchasing decisions. This research aims to analyze the influence of the e-commerce information system implemented by Shopee on consumer purchasing decisions. The research method used was quantitative with a survey approach involving 250 Shopee user respondents. The research results show that ease of use, transaction security, product recommendation features, and customer reviews have a significant influence on consumer purchasing decisions on Shopee. The conclusion of this research is that optimizing information systems in e-commerce can increase the level of consumer trust and tendency to make purchases.